American law in a global context : the basics - Fletcher, George P. (Oxford University Press, 2005)
Whatever your background, if you seek an understanding of the legal system of the United States, this is the book for you. American Law in a Global Context is an elegant and erudite introduction to the American legal system from a global perspective. It covers the law and lawyering tools taught in the first year of law school, explaining the underlying concepts and techniques of the common law used in U.S. legal practice. The ideas central to the development and practice of American law, as well as constitutional law, contracts, property, criminal law, and courtroom procedure, are all presente.